A developmental fMRI study of self‐regulatory control - Marsh, Rachel (Wiley Subscription Services, Inc., A Wiley Company, 2006)
We used functional magnetic resonance imaging (fMRI) to investigate the neural correlates of self‐regulatory control across development in healthy individuals performing the Stroop interference task. Proper performance of the task requires the engagement of self‐regulatory control to inhibit an automatized response (reading) in favor of another, less automatic response (color naming). Functional MRI scans were acquired from a sample of 70 healthy individuals ranging in age from 7 to 57 years. We measured task‐related regional signal changes across the entire cerebrum and conducted correlation analyses to assess the associations of signal activation with age and with behavioral performance. The magnitude of fMRI signal change increased with age in the right inferolateral prefrontal cortex (Brodmann area [BA] 44/45) and right lenticular nucleus. Greater activation of the right inferolateral prefrontal cortex also accompanied better performance. Activity in the right frontostriatal systems increased with age and with better response inhibition, consistent with the known functions of frontostriatal circuits in self‐regulatory control. Age‐related deactivations in the mesial prefrontal cortex (BA 10), subgenual anterior cingulate cortex (BA 24), and posterior cingulate cortex (BA 31) likely represented the greater engagement of adults in self‐monitoring and free associative thought processes during the easier baseline task, consistent with the improved performance on this task in adults compared with children. Although we cannot exclude the possibility that age‐related changes in reading ability or in the strategies used to optimize task performance were responsible for our findings, the correlations of brain activation with performance suggest that changes in frontostriatal activity with age underlie the improvement in self‐regulatory control that characterizes normal human development. Hum Brain Mapp, 2006. © 2006 Wiley‐Liss, Inc.